STUDY OF GLUCOSE-6-PHOSPHATE DEHYDROGENASE ENZYME AND ISOPROSTANE ON PREECLAMPSIA WITH NIFEDIPINE, METHYLDOPA, AND MAGNESIUM SULFATE THERAPY - Lina Lukitasari, - (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this research is to measure erythrocyte glucose-6-phosphate dehydrogenase (G6PD) enzyme activity and isoprostane and to correlate enzyme activity of G6PD with proteinuria and isoprostane in pregnant with proteinuria after the administration of nifedipine, methyldopa, and magnesium sulfate. Methods: This cross-sectional study was held in Soewandi Hospital, Surabaya, East Java, Indonesia. This study used total sampling as much as 30 pregnant women with proteinuria who got nifedipine, methyldopa, and magnesium sulfate administration, age ranged from 17 to 48 years during their third trimester (>20 weeks). G6PD enzyme activity was measured from plasma by spectrophotometric method; plasma isoprostane was measured by competitive-ELISA method; and proteinuria urine spot was analyzed by urine dipstick from standardized laboratory of the hospital. Statistical analysis used in this study was Spearman’s correlation coefficient. Results: In this research, the effect of proteinuria +1 (OR=0.056) is lower than proteinuria +3 level on the presence of high G6PD enzyme activity, and proteinuria +2 (OR=0.933) is lower than proteinuria +3 level on the presence of high G6PD enzyme activity in pregnant women with proteinuria. G6PD enzyme was positively correlated (p=0.08) with proteinuria, and the connection was statistically significant. There was no significant statistic correlation between G6PD enzyme activity and isoprostane concentration (p=0.797). Conclusion: This study found correlations between the enzyme activity of G6PD and proteinuria as the marker of renal damage in pre-eclampsia (PE) with the administration of nifedipine, methyldopa, and magnesium sulfate. However, it had no correlation with isoprostane as the marker of oxidative stress. This study suggests that there should be a concern about understanding the pathophysiology of proteinuria for possibility of drug target for individuals with PE.